2016
DOI: 10.1016/j.drugalcdep.2016.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Spatial relationships between alcohol-related road crashes and retail alcohol availability

Abstract: Background This study examines spatial relationships between alcohol outlet density and the incidence of alcohol-related crashes. The few prior studies conducted in this area used relatively large spatial units; here we use highly resolved units from Melbourne, Australia (Statistical Area level 1 [SA1] units: mean land area = 0.5 km2; SD = 2.2 km2), in order to assess different micro-scale spatial relationships for on- and off-premise outlets. Methods Bayesian conditional autoregressive Poisson models were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 21 publications
2
19
0
1
Order By: Relevance
“…A large literature consistently shows that outlet density is associated with physical AHTO, such as violent crime [41,58] and child abuse [59], as well as alcoholinvolved motor vehicle crashes [60][61][62]. Our analysis detected associations between bar density and drivingrelated harms.…”
Section: Discussionmentioning
confidence: 51%
“…A large literature consistently shows that outlet density is associated with physical AHTO, such as violent crime [41,58] and child abuse [59], as well as alcoholinvolved motor vehicle crashes [60][61][62]. Our analysis detected associations between bar density and drivingrelated harms.…”
Section: Discussionmentioning
confidence: 51%
“…Per capita serving for on-premise consumption and selling for off-premise consumption showed a non-significant bivariate relationship to MV injury, while alcohol-related MV crash injury per road mile showed an inverse relationship for both on-premise and off-premise alcohol establishments. Previous studies in California and elsewhere found positive associations between bar density and risk of alcohol-related MV crashes [28,29,30,31,32] although it should be noted that some of these studies also included property damage only crashes as well as those producing injury or did not control for other environmental factors such as rurality, geographic proximity to an urban area, socioeconomic factors or alternative transportation availability and accessibility.…”
Section: Discussionmentioning
confidence: 99%
“…Demographic (e.g., age, gender, ethnicity, birthplace) and community indicators of instability (e.g., percent 150% below federal poverty level, percent unemployed, percent owner‐occupied housing) were included in the model to control for factors previously found to be associated with DUI or alcohol‐related crashes (Gruenewald et al, 2002; Gruenewald and Ponicki, 1995; Lipton et al, 2018; Morrison et al, 2016). Two additional indicators were included as control variables: “Non‐DUI arrests per capita” controls for the level of police enforcement activity in each LERA and a “County‐residual area” indicator controls for the possible differences in DUI arrest rates in unincorporated (usually rural) areas relative to rates in towns and cities.…”
Section: Methodsmentioning
confidence: 99%